The antecedents and postcedents of satisfaction in business-to-business relationships in South Africa - Mornay Roberts-Lombard; Mercy Mpinganjira; Goran Svensson (South African Journal of Business Management, 2019)
Background: A relationship marketing approach to the management of business relationships can enhance overall customer satisfaction and reduce economic risks, such as opportunism that is associated with business dealings.Aim: The aim of this study was to establish whether a positive relationship exists between trust and commitment, whether trust has a positive influence on commitment, whether trust and commitment positively influence satisfaction and whether opportunism and conflict are outcomes of satisfaction in South African buyer–supplier relationships.Setting: Top 500 companies operating in the South African private sector.Methods: Using a structured questionnaire, data were gathered from 250 large companies in South Africa and were analysed through the application of structural equation modelling (SEM).Results: The findings indicate that both trust and commitment were perceived as important antecedents of satisfaction in a South African business-to-business environment, and that trust is a precursor to commitment in relationship building between organisational buyers and sellers in South Africa. This study adds value by assisting business-to-business buyers and sellers in South Africa on variables to consider when developing relationship-building strategies.Conclusion: Both parties to a relationship should therefore build relationships founded on trust and commitment. This will enhance their joint satisfaction, resulting in less opportunism and conflict, and will foster long-term relationship building based on mutual satisfaction. In contrast, dissatisfaction could increase opportunism and conflict between the parties, leading eventually to the termination of their business relationship.
Keywords: 650